2011
DOI: 10.1111/j.1439-0426.2010.01664.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the prebiotics Immunoster and Immunowall on growth performance of juvenile beluga (Huso huso)

Abstract: The objective of this study was to determine the effects of the prebiotics Immunoster and Immunowall (two commercial prebiotics) on growth performance of juvenile beluga (Huso huso). Prior to the feeding trials, fish were fed the basal diet to apparent satiation four times per day for a 4-week acclimatization period. The basal diet contained 42% crude protein, 14.5% crude lipid, 10.06% ash and 6.1% moisture. Then, 450 beluga juveniles weighing 95.6 ± 9.4 g were randomly distributed into 15 fiberglass tanks (2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Many previous studies have demonstrated similar effects in aquatic animals (Staykov et al, 2007;Torrecillas et al, 2007;Burr et al, 2008;Taati et al, 2011;Amirkolaie et al, 2013). Colonization by beneficial bacteria that were induced by the consumption of dietary Immunogen ® may account for these positive impacts.…”
Section: Discussionmentioning
confidence: 65%
“…Many previous studies have demonstrated similar effects in aquatic animals (Staykov et al, 2007;Torrecillas et al, 2007;Burr et al, 2008;Taati et al, 2011;Amirkolaie et al, 2013). Colonization by beneficial bacteria that were induced by the consumption of dietary Immunogen ® may account for these positive impacts.…”
Section: Discussionmentioning
confidence: 65%
“…Our results indicate that supplementation with β-G and MOS (0.3% in feed by weight) improved growth performance in and feed utilization by Nile Tilapia. Use of prebiotics containing β-G and MOS was previously found to improve the growth performance of Common Carp Cyprinus carpio, Beluga Huso huso, and sea cucumbers Apostichopus japonicus (Gu et al 2011;Ta'ati et al 2011;Ebrahimi et al 2012). Ye et al (2011) reported that the use of two types of prebiotic (fructooligosaccharides and MOS) in the diets of Olive Flounder Paralichthys olivaceus yielded better growth performance than the use of a single product.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, in this research the maximum level of RPC inclusion in sturgeon diet was 53 % and at this level the dietary protein was almost completely RPC protein. Even if we decided to not analyze productive results, we interestingly observed that the specific growth rate (SGR) was 5 times better than the case of white sturgeon (A. transmontanus) (Gawlicka et al, 2002), and the productive parameters were also better than Beluga sturgeon (Hosseini et al, 2010;Ta'ati et al, 2011), "AL" hybrid sturgeon , hybrid sturgeon (Acipenser schrenckii x Huso dauricus) (Qiyou X. et al, 2011) and white sturgeon (Lin et al, 1997).…”
Section: Discussion Diets and Fish Growthmentioning
confidence: 98%